Primary Educators Experts’ Validation of The Developed Mathematics Mobile Application to Enhance the Teaching of Mathematics in Nigeria Primary Schools - Eyiyemi Veronica Omolafe (ASEAN Journal of Science and Engineering Education, 2021)
Mobile learning brought a great benefit to education through, training at any time; training at the place; learner-centered content; and development of teaching and learning. Smartphones and similar mobile devices have changed the way individuals interact with technology and with each other. To ascertain the usability of the instructional mobile application, it must be verified by experts in the area of the subject content. Hence, it is needed to determine the experts’ validation of the developed mathematics mobile application before it can be used for instructional purposes. Two instruments were used for the validation process: Primary Education Lecturers’ Rating Scale and Primary School Teachers’ Rating Scale. Percentage score and mean were used to answer research questions. The percentage score of the rating for the validation of the developed mathematics mobile application by the six Experts shows that the mobile application satisfied the required standard in the field of primary education. The developed mathematics mobile application has the potential to make teaching and learning basic mathematics easy and interesting. The study revealed that teachers can teach the concept of mathematics to primary school pupils either individually or collaboratively through effective utilization of the mobile application. It was recommended that primary educators should employ a mobile application strategy for teaching those abstract and difficult concepts in mathematics.